Phase I trial of the androgen receptor modulator CR1447 in breast cancer patients. Issue 7 (October 2017) - Zweifel, Martin; Thürlimann, Beat; Riniker, Salome; Weder, Patrik; von Moos, Roger; Pagani, Olivia; Bigler, Martin; Rothgiesser, Karin M; Pilop, Christiane; Hawle, Hanne; Brauchli, Peter; Tapia, Coya; et al.
Abstract : CR1447 (4-hydroxytestosterone, 4-OHT) binds to the androgen receptor and has antiproliferative activity in both ER-positive and ER-negative/AR-positive breast cancer cells in preclinical studies. The objective of this first-in man trial was to evaluate the safety and to determine the dose of CR1447, administered as an ointment, for Phase II. Escalating doses (100, 200, 400 mg) of CR1447 were administered topically on a daily basis to patients with ER-positive/AR-positive/HER2-negative advanced breast cancer pretreated with several lines of therapy. 14 patients have been treated for a total of 42 cycles. Two patients, one at dose level 100 mg and one at dose level 200 mg, showed early tumour progression and were replaced. Related adverse events were all ≤ grade 2 and included fatigue, bone and joint pain, stiffness, dry skin and mouth, nausea, sweating, urinary tract infection, rash, headache and distress. No drug-related dose-limiting toxicities (DLTs) were seen. Two patients (17%) achieved stable disease at 3 months. Pharmacokinetic analysis confirmed dose-dependent transdermal uptake of CR1447. 4-OH-androstenedione (4-OHA), a key metabolite of 4-OHT, was undetectable in most of the plasma samples. Urine metabolites of 4-OHT and 4-OHA indicate high exposure of 4-OHT after topical administration. Oestradiol serum concentrations did not increase, confirming preclinical data that CR1447 is not converted to estrogens in vivo . In conclusion, CR1447 administered transdermally as an ointment is well tolerated and appears to have single-agent activity in heavily pretreated ER-positive/HER2-negative breast cancer patients. The recommended phase II dose is 400 mg/day.